The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5194/angeo-34-691-2016
|View full text |Cite
|
Sign up to set email alerts
|

Modified ion-Weibel instability as a possible source of wave activity at Comet 67P/Churyumov-Gerasimenko

Abstract: Abstract. We analytically discuss wave excitation in a homogeneous three component plasma consisting of solar wind protons, electrons and a beam of cometary water ions applied to the plasma environment of comet 67P/Churyumov-Gerasimenko. The resulting dispersion relations are studied in a solar wind rest frame, where a cometary current is solely generated by the water ion beam, and a cometary rest frame representing the rest frame of the Rosetta spacecraft. A modified ion-Weibel instability is excited by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 42 publications
3
52
1
Order By: Relevance
“…Prominent features are the increase in Bo and the rotation in the field direction. Detailed analyses of the magnetic field indicate the disappearance of low-frequency waves (tens of mHz), usually observed in the close plasma environment of the comet (Richter et al 2015(Richter et al , 2016Koenders et al 2016;Meier et al 2016), at the time of the outburst (see Sects. 2.3 and 2.4).…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prominent features are the increase in Bo and the rotation in the field direction. Detailed analyses of the magnetic field indicate the disappearance of low-frequency waves (tens of mHz), usually observed in the close plasma environment of the comet (Richter et al 2015(Richter et al , 2016Koenders et al 2016;Meier et al 2016), at the time of the outburst (see Sects. 2.3 and 2.4).…”
Section: Observationsmentioning
confidence: 99%
“…7. Small yellow and green regions within the frequency range of ∼10-100 mHz in the frequency spectrum indicate magnetic "singing comet waves" (Richter et al 2015(Richter et al , 2016Koenders et al 2016;Meier et al 2016). These singing comet waves disappear or become weakened between ∼1000 and 1300 UT, as shown by the reduced wave amplitudes shown in the right panels.…”
Section: Wave Characteristics During the Cometary Outburstmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of the plasma environment of 67P/Churyumov-Gerasimenko was performed by Odelstad et al (2015), who reported electron temperatures around 5 eV. Low frequency wave activity -the peak of the spectrum at approximately 40 mHz -was discovered by Richter et al (2015), observed simultaneously at two points by Rosetta and the Philae lander , and has been interpreted in terms of a modified ion-Weibel instability (Meier et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Two mechanisms have been discussed in literature thus far: (i) heating of electrons through wave particle interactions, such as the singing comet waves (understood as an ion Weibel instability [43,52]) or lower hybrid waves [45], and (ii) the acceleration of electrons along the ambipolar electric field [29]. In the second scenario, solar wind electrons traveling toward the comet fall into the potential well that is generated by the gradient in electron number density [53,54].…”
mentioning
confidence: 99%